The Tourist Happiness Level after Participating in Yoga Activities in Ubud - Hartika, Listiyani Dewi; Gunawan, Angelia Natasya; Dhermawan, Made Bagas Aldi (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
This study aimed to examine the level of tourist happiness after participating in yoga activities in Ubud, Bali, a destination widely recognized for spiritual and welness tourism. A quantitative descriptive approach was employed, involving 100 toursits aged 18-30 years selected by purposive sampling. Data were collected using the oxford Happiness Questionnaire, which demonstrates high reliability.